2017
DOI: 10.1111/jppi.12222
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Video Monitoring in Medicaid Home and Community‐Based Services Waivers for People With Intellectual and Developmental Disabilities

Abstract: While the number of available caregivers for people with intellectual and developmental disabilities (I/DD) is reducing, the number of people who need care and support is steadily increasing, effectively creating a vacuum of care. In response to this increasing problem, and as a result of advances in technology, telecare, and remote monitoring in the long‐term support of people who are aging or have I/DD are becoming more prominent. Despite noted benefits, telecare and other forms of technological surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…Regarding the latter category, eHealth is mostly used as an instrument to support the learning of specific daily living or vocational skills, and much less as a self-supportive tool or remote professional support (Oudshoorn et al 2020;Vázquez et al 2018). Although this indicates that studies regarding the use of remote support for daily functioning are still relatively scarce, the practice of offering remote online support has been expanding and is expected to continue doing so in the years to come (Friedman and Rizzolo 2017;Tassé, Wagner, and Kim 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter category, eHealth is mostly used as an instrument to support the learning of specific daily living or vocational skills, and much less as a self-supportive tool or remote professional support (Oudshoorn et al 2020;Vázquez et al 2018). Although this indicates that studies regarding the use of remote support for daily functioning are still relatively scarce, the practice of offering remote online support has been expanding and is expected to continue doing so in the years to come (Friedman and Rizzolo 2017;Tassé, Wagner, and Kim 2020) .…”
Section: Introductionmentioning
confidence: 99%
“…Launched in May 2018, the General Data Protection Regulation (GDPR) is the novel European Union-wide law on data protection a significant step towards more responsible protection of individuals (Crutzen et al, 2019). While it is recognized that participation in research is based on affirmative, unambiguous, voluntary, informed, and specific consent (Mendelson, 2018), people with advanced dementia or intellectual and developmental disabilities are not able to give informed consent or understand the consequences of data acquisition (Friedman and Rizzolo, 2017;Chalghoumi et al, 2019;Timmers et al, 2019). Article 6 of the GDPR addresses this issue by including provisions that protecting persons with dementia and their relatives from being coerced into providing consent without awareness of how their data will be used (Cool, 2019;Crutzen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Friedman et al USA (Friedman and Rizzolo, 2017) 2017 National I/DD survey on electric video monitoring Video monitoring are effective methods to expand community care while being cost effective. However, it should also aim at improving care, not only serve as a substitute for personal care and interaction.…”
Section: Limitationsmentioning
confidence: 99%
“…Professional support for people with intellectual disabilities is increasingly provided remotely through the use of online devices like smartphones, computers and tablets (Friedman & Rizzolo, 2017; Taber‐Doughty et al, 2010; Tassé et al, 2020). Research has shown that a remote provision of support can have several benefits, such as an enhanced efficiency in services and an increased accessibility of support (e.g., Brewer et al, 2010; Cullen et al, 2012; de Wit et al, 2015; Niemeijer et al, 2010; Zaagsma, Volkers, Koning, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As remote support is expected to become more common in the field of intellectual disability (Friedman & Rizzolo, 2017; Tassé et al, 2020), it is important to understand the specificities and complexities that come with the task of providing professional support remotely. The purpose of this paper is to contribute to this understanding by exploring the experiences of support staff of the Dutch remote support service DigiContact.…”
Section: Introductionmentioning
confidence: 99%